THE FACTORS AFFECTING TRANSFER PRICING DURING COVID-19 WITH PROFITABILITY AS A MODERATING VARIABLE - Jasmine; Fahmi Natigor Nasution; Isfenti Sadalia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The purpose of this study is to examine and analyze whether tax rates, exchange rates, bonus mechanisms, and leverage affect transfer pricing, with profitability as a moderating variable, in healthcare subsector companies listed on the Indonesia Stock Exchange during COVID-19 period and the post-COVID-19 period. The research data were collected through documentation techniques by accessing secondary data from the official website of the Indonesia Stock Exchange. The sampling method used was purposive sampling. Hypothesis testing was conducted using moderated regression analysis. The results show that during the COVID-19 period, tax rates, bonus mechanisms, and leverage have an effect of transfer pricing. In addition, profitability is able to moderate the effect of tax rates on transfer pricing but does not moderate the other variables. In the post-COVID-19 period, tax rates and leverage affect transfer pricing, whereas exchange rates and bonus mechanisms do not have a significant effect. Furthermore, profitability is not able to moderate the effect of any variables on transfer pricing in the post-COVID-19 period.